2018
DOI: 10.1111/jocn.14119
|View full text |Cite
|
Sign up to set email alerts
|

Nursing staff intentions towards managing deteriorating health in nursing homes: A convergent parallel mixed‐methods study using the theory of planned behaviour

Abstract: Managers implementing hospital avoidance programs should consider the role of referents, appraise the known barriers and facilitators and take steps to identify those unique to their local situation. All levels of nursing staff play a role in preventing hospitalisation and should be consulted in the design, implementation and evaluation of any hospital avoidance strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 46 publications
0
27
0
Order By: Relevance
“…Factors that influence the identification of acute deterioration were inferred from a variety of study types reporting problems experienced by residential aged care staff when determining acute deterioration (Laging et al, 2018), factors influencing the decision to transfer a resident to hospital (Laging et al, 2015), and outcomes of hospital avoidance interventions (Little et al, 2019; O'Neill et al, 2017a; O'Neill et al, 2018). In addition, reported perceptions of the deteriorating resident, from the perspective of personnel (O'Neill et al, 2017b), using or developing early warning systems for aged care (Stocker et al, 2021), illness identification in the acute infection context (Longo et al, 2004), and problems identified while developing and validating a standardized illness warning instrument informed factors (Boockvar et al, 2000).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Factors that influence the identification of acute deterioration were inferred from a variety of study types reporting problems experienced by residential aged care staff when determining acute deterioration (Laging et al, 2018), factors influencing the decision to transfer a resident to hospital (Laging et al, 2015), and outcomes of hospital avoidance interventions (Little et al, 2019; O'Neill et al, 2017a; O'Neill et al, 2018). In addition, reported perceptions of the deteriorating resident, from the perspective of personnel (O'Neill et al, 2017b), using or developing early warning systems for aged care (Stocker et al, 2021), illness identification in the acute infection context (Longo et al, 2004), and problems identified while developing and validating a standardized illness warning instrument informed factors (Boockvar et al, 2000).…”
Section: Resultsmentioning
confidence: 99%
“…Few factors that relate specifically to consumers were identified (6%; 3/52). Three subcategories within this grouping include consumers' knowledge of the resident which provides clues to the resident's deterioration (Longo et al, 2004), social pressures placed on care staff from the consumers to detect early deterioration (O'Neill et al, 2018), and residential aged care facility staff's perception of being undervalued when consumers rate their expertise less than that of hospital staff (O'Neill et al, 2017b).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The phenomenon of AD was studied as part of a wider eld of interest and as such, contextual factors surrounding AD may have been missed by these studies. This literature considers many contributing factors to hospital admission, including shared decision making, prognostication, advance care plans, the roles of multiple professionals and evaluations of hospital avoidance programmes 27,[30][31][32] . However, it does not consider the cascade of events that lead to care home staff identifying residents at risk of deterioration, or their decision to seek help external to the care home.…”
Section: Discussionmentioning
confidence: 99%
“…According to Flemming (2007), the methodological divide of qualitative and quantitative research is more entrenched in the nursing discipline, reflecting the medical hegemony in healthcare research, where randomized controlled trials dominate. That said, its use has intensified to the point where a scoping exercise, searching titles in CINAHL, showed that from January 2017–May 2018, 748 MMR studies were published in journals relevant to nursing, covering subjects as diverse as assessing students in practice (Burden, Topping, & O'Halloran, 2018) to managing deteriorating health in nursing homes (O'Neill, Dwyer, Reid‐Searl, & Parkinson, 2018). Over the years many authors have justified the use of the approach as one that has the power to uncover important evidence that may otherwise be overlooked.…”
Section: Introductionmentioning
confidence: 99%